GENERAL VIEWS OF STUDENTS ABOUT THE QUALITY OF SERVICE AND THEIR SATISFACTION LEVEL IN THE HIGHER EDUCATION CREDIT AND HOSTELS INSTITUTION (AFYONKARAHİSAR-TINAZTEPE DORMITORY SAMPLE) - Süleyman KARATAŞ (Fırat University, 2019)
The purpose of this study is to determine general views of students about the quality of service and their satisfaction level in the Higher Education Credit and Hostels Institution. The study group, comprising of 442 randomly chosen students, stay at Tınaztepe Dormitory within the borders of Afyon Kocatepe University and study at the Faculty of Education, Faculty of Science, Faculty of Engineering, and the Faculty of Economics and Administrative Sciences Faculty of Veterinary Medicine. To gather the data of this study, "Higher Education Credit and Hostels Institution and for service quality and student satisfaction survey Form" was used. In addition to descriptive statistics, t-test, ANOVA techniques were used to analyse the data. According to the findings, (1) canteens, fast food restaurants should be more sensitive about hygiene, (2) there is a lack of facilities for students to spend their free times, (3) psycho-social service staffs are not able to give consultation to students and (4) some problems occur while implementing dormitory rules.